Global Financial Crisis, Financial Contagion, and Emerging Markets - Ozkan, F. Gulcin; Unsal, Filiz (Washington, D.C. : International Monetary Fund, 2012)
The recent global financial crisis was the first in recent history that was triggered by problems in the financial system of the mature economies. Existing work on financial crisis in emerging market countries, however, almost exclusively focus on the role of financial frictions in the domestic economy. In contrast, we propose a two-country DSGE model to investigate the transmission of a global financial crisis that originates from financial frictions in the rest of the world. We find that the scale of financial spillovers from the global to the domestic economy and trade openness are key determinants of the severity of the financial crisis for the domestic economy. Our results also suggest that the welfare ranking of alternative monetary policy regimes is determined by the degree of financial contagion, the degree of trade openness as well as the scale of foreign currency denominated debt in the domestic economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet